STUDI FAKTOR SUHU DI DALAM RUMAH DAN KEJADIAN DEMAM BERDARAH DENGUE DI SEMARANG TAHUN 2017 - Rahmah Putri Sunarno; Nur Endah Wahyuningsih; Anto Budiharjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by dengue virus and transmitted by Aedes aegypti and Aedes albopictus. In 1968 the Incidence Rate (IR) of this disease was 0.05 per 100.000 population and it increased to 49.5 per 100.000 population in 2015. Data of DHF in Semarang City from 2012 to 2016 showed that the incidence trend of this disease increased. For five years from 2010 to 2016, Semarang City was in the top three rankings of DHF IR in Central Java. The case of dengue fever in Indonesia is closely related to environmental conditions such as temperature inside the house. This aim of this study was to describe temperature inside the house and dengue in the productive age (13-60 years) in Semarang City. The subjects were 54 people consisted of 27 cases and 27 controls and selected by consecutive sampling. The source of this study was the primary data from observation and measurement of temperature inside the house using a thermohygrometer. These measurements did after the subjects of dengue case were health. The result showed that the proportion of subjects who lived at house with ≥25°C – ≤30°C temperature (Aedes aegypti’s optimal temperature for breeding) were mostly in the control group (37%). While the proportion of subjects who lived at house with <25°C or >30°C temperature (not an optimal temperature for Aedes aegypti’s breeding) were mostly in the case group (81,5%).